African swine fever in Benin and prevalence of the disease in Southern Benin: A retrospective study (2014–2018) - Ohouko, Okri Fréjus Hans; Koudouvo, Koffi; Dougnon, Tossou Jacques; Agbonon, Amegnona; Karim, Issaka Youssao Abdou; Farougou, Souaïbou; Gbeassor, Messanvi (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aimed to assess the prevalence and risk factors of African swine fever (ASF) disease in Benin. Materials and methods: A retrospective study was conducted on 70 pig farms from the Departement of Atlantique and Ouémé and also by using the data available from the Directorate of Livestock on the spread of ASF in Benin from 2014 to 2018. The prevalence of ASF was assessed with 106 nasal swabs from apparently healthy domestic pigs and 15 organ samples from dead ASF-suspected pigs. ASF virus detection was carried out by conventional polymerase chain reaction using Qiagen Kit for DNA extraction. Data recorded were processed with SAS software (2006). Results: It appears that ASF is an endemic disease in Benin with the Department of Ouémé as the hotspot of dissemination of the virus in the country. The losses due to ASF recorded from 2014 to 2018 are evaluated to 884,850,000 CFA Franc by estimating the average cost of a pig at 25,000 FCFA. A prevalence of 1.89% (CI at 95%, 0.71–3.49) was recorded for live animals with a positive result in organs from all dead pigs suspected of ASF. Breeding practices related to the sharing of breeding males, scavenging pigs, and non-compliance with biosecurity measures were the risk factors identified. Conclusion: The present study sheds light on the areas prone to the ASF virus in Benin. Moreover, the cross-sectional data recorded on the prevalence of ASF will help to better rule on the spread of the disease. It would be interesting for the Beninese Republic to increase its efforts for ASF control. J. Adv. Vet. Anim. Res., 7(3): 464-470, Sep 2020 http://doi.org/10.5455/javar.2020.g442